Fight game - Wild, K. (Kate), 1954- (Chicken House/Scholastic, 2009)
Gypsy boy Freedom Smith, a born fighter, makes a deal with the police after being arrested for a crime he did not commit, and agrees to go undercover to infiltrate a high-tech fight club that is targeting street kids.